Acute Hepatitis by Bartonella henselae Infection in an Adult Patient with Decompensated Liver Cirrhosis - Jorge Alonso Garay Ortega; Louis Fernando Robles Fernandes; Vianey Guadalupe Tellez Bolaños; Karla Paulina Sandoval Mosqueda; Karla Daniela Salgado Guizar (Journal of Renal and Hepatic Disorders, 2023)
Hepatitis caused by Bartonella henselae in adults is a condition that is seldom reported in the literature, as well as its current incidence and prevalence. While there is a broad spectrum of well-defined and established clinical entities, hepatic involvement represents the third most frequent clinical manifestation of infection by this genus of bacteria. It may or may not be characterized by the presence of hepatosplenic granulomas. Diagnosis requires a high level of clinical suspicion, exclusion of additional etiologies, and a causal relationship with risk factors. Polymerase chain reaction is the diagnostic test with the highest diagnostic yield, and treatment varies depending on the clinical expression. We describe the case of an adult patient with hepatitis secondary to Bartonella henselae infection.